The extermination and conservation of the American bison - Lueck, Dean (The Journal of legal studies, 2002)
The dramatic near extinction, and subsequent recovery and restoration, of the American bison during the late nineteenth century is examined using a property rights model of renewable resource production. The paper considers the implications of bison exploitation under open-access, common-ownership, and private-property regimes and further examines how these regimes are determined. Implications are tested against historical and anthropological data on bison populations, robe and hide prices, cattle-stocking rates, American military behavior, Indian tribal territories, federal land policy, the costs of harvesting bison, and formal and informal property rights regimes. The study uncovers the details of this famous story in American wildlife conservation and sheds light on the role of markets in extinction and preservation and the evolution of property rights to such large-scale natural resources.